KARAKTERISTIK DAN STRATEGI INOVASI PENDIDIKAN - Bagus Hidayattullah; Tri Alawiyah; Karoma Karoma; Mardiah Astuti (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
This article discusses the characteristics and strategies of educational innovation, innovation in education is needed, so that there are changes and provide something new that can improve the quality of education both nationally and internationally. In realizing educational innovation, a characteristic is needed that can provide color in the innovation itself. And in its implementation requires a decision process that is really mature and not in a hurry. Before becoming a decision, the innovation usually starts from a diffusion which is then systematically arranged and designed to conduct a trial which later turns into dissemination, which is a process of applying innovations that already have results and are considered successful. And the success itself requires a strategy so as not to miss the target and can be used as well as possible, so that the innovation itself really becomes something new and has a positive impact.